THE IMPACT OF CASH HOLDING ON FIRM VALUE (CASE STUDY ON NON-FINANCIAL COMPANIES IN THE ASEAN CAPITAL MARKET) - Ra’no Shamsiddinova; Mimin Widaningsih; Elis Mediawati (Yayasan Nuraini Ibrahim Mandiri, 2026)
The aim of this research is to investigate the role of cash holdings in providing financial flexibility, supporting operations, and capturing investment opportunities within the ASEAN capital market. The research sample consists of 216 companies selected using purposive sampling based on specific criteria determined by the researcher. The sample includes 82 companies from Indonesia, 93 companies from Malaysia, and 41 companies from Singapore. The observation period covers three years, from 2022 to 2024, in order to capture recent financial conditions and firm performance. This study uses a quantitative research approach with simple linear regression analysis to test the proposed hypothesis. In this research, cash holding acts as the independent variable, while firm value is the dependent variable. The regression analysis is conducted using statistical software to obtain accurate estimation results. The findings show that cash holding has a positive and significant effect on firm value, indicating that companies with higher levels of cash holding tend to have higher firm value because cash provides financial flexibility and helps companies manage financial risks and investment opportunities. However, this study has several limitations, including the use of only one independent variable and a sample limited to non-financial companies in the ASEAN capital market. Therefore, future research is recommended to include additional variables and expand the research scope to obtain more comprehensive results.